Commercializing Sustainable Innovations in the Market through Entrepreneurship - Keskin, D.; Brezet, H.; Diehl, J. C. (Cranfield University Press, 2009)
The system innovations for sustainability require changes at multiple-domains (social, cultural, institutional and technological) and multiple-levels (micro-, meso-, and macro-levels) of the socio-technological system. From a sustainable production and consumption view, systems innovations can be enhanced through a PSS strategy at organisational level. This can be achieved through new entrepreneurial entries because of their potential in commercialising sustainable innovations and consequently bringing the necessary institutional change that favours such innovations. This paper aims at investigating how sustainability-driven entrepreneurs enhance the commercialisation of sustainable PSS and the consequences of this process and the potential role of design in it.
Organised by: Cranfield University
Keywords: Sustainability; (Product-Service) System Innovations; Entrepreneurship